APLIKASI ABSENSI GURU PADA SEKOLAH BERBASIS ANDROID DENGAN KEAMANAN QR CODE (STUDI KASUS : SMP NEGERI 4 BATANG GANSAL) - Rahmalisa, Uci; Irawan, Yuda; Wahyuni, Refni (Riau Journal Of Computer Science, 2020)
Attendance is a part of the important role in every educational institution. Where attendance is one of the main supporting that can support and motivate every activity done. As in the absence of attendance at the 4 Batang Gansal Junior High School that performs signatures on paper and writes the entry time at the teaching hour in which case this can result in fraud due to the uncontrollable level of discipline. The administration also difficult to make reports and convey attendance information to each teacher regarding the recording of the present time as well as the time recording of the work because the report is still created using Microsoft Excel, in this way can be mistyped data and the deletion of data. The purpose of this research is to design and build an Android application that makes it easy for teachers to perform attendance at school, an application that utilizes Qr Code as the main component in assisting attendance process every teacher. Based on the above statement, the application of Qr Code technology in attendance system in junior high school teacher 4 Batang Gansal with Android device can accelerate the attendance process, in the results of the system test has been completed and successfully created, the system will be implemented immediately on the Android smartphone. Based on the research result of the creation of attendance application in Android based schools with the security of this Qr Code then it can be concluded that the research resulted in the teacher attendance application in Android based schools with Qr Code security which can be able to process attendance. In the test results of the system that has been completed and successfully created, the system will be implemented immediately on the Android smartphone and this application can also provide information about the attendance in the form of charts.